Exploring the Social Media Practices of Environmental Non-Governmental Organizations (ENGO): A Qualitative Approach - DELLECH, Dorsaf; KLABI, Fethi; MERZOUGUI, Souhaila; DEBABI, Moez (Journal of Ecohumanism, 2024)
This study aims to enhance the understanding of how Environmental Non-Governmental Organizations (ENGOs) use social media to engage their audiences in the causes they advocate. By incorporating elements from the Uses and Gratification theory and other sources, the researchers conducted one-on-one interviews with 20 ENGOs. Data were analysed through textual analysis using NVIVO software. The results indicate that ENGOs leverage social media, particularly Facebook, to raise awareness about climate change and biodiversity, with positive impacts on fundraising and lobbying, depending on resource availability. However, limited budgets and corporate governance issues pose challenges to social media use. This study provides managerial recommendations for developing more engaging and effective communication strategies on social media, as well as further exploration of environmental communication trends.